THE EFFECT OF JOLLY PHONICS SONGS ON THE SPEAKING SKILL OF PRIMARY SCHOOL STUDENTS IN DUHOK - NASER, LUREEN I. (Journal of Duhok University, 2023)
The main purpose of this study is to investigate the effect of using Jolly Phonics songs on English-speaking skills among early-grade Kurdish students. Six groups of primary students were selected to take part. Three groups, which consisted of 45 students, were selected as experimental groups. They were taught by using the Jolly Phonics songs for three months. The other three groups, which consisted of 45 students, were selected as control groups. They were taught using traditional teaching methods. The instruments used in this study were Jolly Phonics strategy flashcards and Jolly Phonics songs. Participants’ speaking skills were measured both before and after the teaching period through a specially designed rubric that measured their speech clarity, loudness, detail sharing, eye contact, and interaction. The findings of this study show that the Jolly Phonics songs effectively improve the students’ speaking skills. Students have achieved very high results in all the measured variables because they learn to speak English in a fun way. Moreover, it is an effective method for all students, even those with learning difficulties.